2009
DOI: 10.1073/pnas.0905668106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a region of the DNMT1 methyltransferase that regulates the maintenance of genomic imprints

Abstract: Reprogramming of DNA methylation patterns during mammalian preimplantation development involves the concurrent maintenance of methylation on differentially methylated domains (DMDs) of imprinted genes and a marked reduction of global (non-DMD) genomic methylation. In the developing mammalian embryo, one allele of a DMD is unmethylated, and the opposite parental allele is methylated, having inherited this methylation from the parental gamete. The maintenance of DMDs is important for monoallelic imprinted gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 31 publications
2
55
1
Order By: Relevance
“…These results suggest that ZFP57 is continuously required for maintaining DNA methylation imprint in ES cells, and maintenance of genomic imprinting may be an active process. Similar findings have been discovered previously for the mechanisms of the maintenance DNA methyltransferase DNMT1 in DNA methylation imprint (45,59,60).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results suggest that ZFP57 is continuously required for maintaining DNA methylation imprint in ES cells, and maintenance of genomic imprinting may be an active process. Similar findings have been discovered previously for the mechanisms of the maintenance DNA methyltransferase DNMT1 in DNA methylation imprint (45,59,60).…”
Section: Discussionsupporting
confidence: 75%
“…ES cells have been increasingly employed as a model system for studying genomic imprinting (9,25,(42)(43)(44)(45)(46). Indeed, we found that ZFP57 maintains DNA methylation imprint at a large subset of imprinted regions in ES cells.…”
mentioning
confidence: 64%
“…This suggests that DNMT1 activity is regulated and that noninactivating mutations in Dnmt1 that generate informative mutant methylomes can be found. Based on this notion, we studied the effects on genomic methylation of expressing mutant DNMT1 proteins in ES cells using a Dnmt1 tet/tet line in which the endogenous DNMT1 enzyme is extinguished by the administration of doxycycline (Borowczyk et al 2009). We found that methylome changes were induced by expressing DNMT1 proteins with mutations in its large 300-aa intrinsically disordered domain (IDD)-some IDD mutants produced methylomes specifically lacking gDMD methylation, whereas other mutants produced methylomes retaining normal gDMD methylation but with much reduced global methylation.…”
mentioning
confidence: 99%
“…More recently, it was reported that the zygotically expressed, somatic form of DNMT1, called DNMT1s, maintains the methylation imprints at the other cell cycles of pre-implantation development [49,50]. At present we do not know how the DNMT1 isoforms specifically find the DMRs among many other DNA regions, but a recent study suggested that a mammalian-specific region near the amino terminus of DNMT1 is probably involved in the discrimination [51].…”
Section: Factors Involved In Imprint Maintenancementioning
confidence: 94%